Low haemoglobin density as an anaemic indicator in canine babesiosis - K. Rajamanickam; V. Leela (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Low Hemoglobin Density (LHD) is related to functional iron availability and hemoglobin content. To assess the use of LHD as an anaemic indicator in canine babesiosis, 108 dogs with symptoms of canine babesiosis were selected and screened for disease by polymerase chain reaction. Blood samples were collected for estimating haematological variables, serum iron, TIBC, UIBC and LHD. Based on the haemoglobin, PCV and erythrocyte count the animals were grouped into anaemic and non-anaemic populations. LHD% was higher in the anaemic population (P<0.001) and it was negatively correlated to haemoglobin, packed cell volume, erythrocytes, MCHC and serum iron. LHD% was highly depend on serum iron (P<0.001). Receiver operating characteristics (ROC) curve analysis revealed LHD was 100.00% specific and 80.43% sensitive in identifying the functional iron deficient anaemia with cut-off value of 1.83%. This study reveals that LHD is a cost-effective parameter for identifying the functional iron deficient anaemia in canine babeisosis.